Closure - Hitapriya Suprayitno (Departemen Teknik Sipil, Institut Teknologi Sepuluh Nopember, 2024)
Journal of Infrastructure & Facility Asset Management Volume 6, Special Issue 2, January 2024 (e) ISSN 2656-8896 (P) ISSN 2656-890X JIFAM, Vol.6, Special Issue 1, January 2024 Slope Stability Analysis for Landslide in Road Preservation Working Packages Ende - Wolowaru and Junction – Kelimutu Sta 10+475Fauzan Akbar, Yudhi Lastiasih, Herman Wahyudi & Agustinus Junianto Subgrade Stabilization with Ca(OH)2 Lime to Improve the Physical and Mechanical Properties of Soil (Case Study: The National Road Trengguli – Bts. Kab. Demak/Kudus)Rahmadsyah Rangkuti, Ria Asih Aryani Soemitro, Dwa Desa Warnana, Trihanyndio Rendy Satrya & Yanuar Dwi Putra Comparison of Three Embankment Reinforcement on Soft Soil, A Case Study of Calang – Simpang Peut Road SectionDoni Mardian, Indrasurya B Mochtar & Dedy Mandarsyah Effect of Fly Ash and Bottom Ash on Characteristics of Clay Soil (Case Study: National Road Section Demak – Kudus, Indonesia)Alien Maulida Nurtaqwim, Ria Asih Aryani Soemitro, Dwa Desa Warnana, Trihanyndio Rendy Satrya & Yanuar Dwi Putra Existing Design Analysis of Slope Reinforcement on Clayey Soil and Its modified Alternatives (Case Study : Awunio – Lapuko National Road, Southeast Sulawesi)Zahrial Firman R, Mohamad Khoiri & Freddy Siagian JIFAM, Vol.6, Issue 1, January 2024 Determination of Optimum Mixture Between FABA and Local Fill Soil for Road Embankment. Case study: Road Preservation of Sp. Kereng - Bereng Bengkel – Pilang – Pulang Pisau, Central KalimantanRaden Hisyam Syauqi Al Ghifari, Noor Endah Mochtar & Soendiarto Analysis of Main Road Stability Due to The Effect of River Water Level Fluctuations and Rainfall (Case Study: Trengguli - Kudus Road Section)Akhdiat Fajar Wijaya Kusuma, Ria Asih Aryani Soemitro, Trihanyndio Rendy Satrya& Yanuar Dwi Putra Analysis of Existing Slope Reinforcement Design on Clay Shale Soil and Its Alternative Modifications: A Case Study of the Awunio – Lapuko Road Section Sta 4+955 – 5+015 in the Southeast Sulawesi ProvinceA. Azhari, Khoiri & Freddy Analysis of Road Embankment Improvement on Soft Soil Using Foamed Mortar Lightweight EmbankmentAlfiady Reza Permana Putuarga, Indrasurya B. Mochtar & Dedy Mandarsyah Determination of the Percentage Ca(OH)2 Lime Stabilization Material for Weathered Clay Shale as Road Subgrade on Serang – Panimbang Toll Road Section III STA 57+200Prince Joy Sormin, Trihanyndio Rendy Satrya, Mahendra Andiek Maulana & Wahyu Supriyo